A longitudinal study on lecture listening difficulties and self-regulated learning strategies across different proficiency levels in EMI higher education - Zhou, S; Rose, H (De Gruyter, 2024)
The absence of language admission thresholds in many English medium instruction (EMI) university programmes has led to marked heterogeneity in students’ English proficiency upon entry. These students may face diverse challenges when listening to academic lectures, adopt different strategies to cope, and undergo varying trajectories in listening over time. To unpack such complexities, this study adopts a longitudinal mixed-methods design, comprising questionnaire responses from 412 freshmen and semi-structured interviews with 34 students at the beginning, halfway, and end of their first semester studying at an EMI university in China. Students were divided into high, medium, and low proficiency cohorts based on their listening placement test scores. Multilevel modelling analyses highlight that students entering with lower proficiency reported sharper reductions in listening challenges over time. Interview findings also reveal that these students engaged in more industrious self-regulated listening practice outside of the classroom than their highly proficient peers. Regardless of disparities in students’ proficiency, all students developed a higher tolerance towards ‘non-native’ teacher accents and shifted attitudes towards handling disciplinary terminology. The findings offer pedagogical implications for supporting different groups of students’ needs for successful transitions into English-medium tertiary education.